1979
DOI: 10.1007/bf00569351
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a correlation between late replication and autosomal gene inactivation in a familial translocation t(X;21)

Abstract: A familial translocation t(X;21)(q2700;q11) is studied. A girl, trisomic for almost all the chromosome 21, has a mildly abnormal phenotype. A second girl, phenotypically abnormal, is monosomic for the juxtacentromeric region of chromosome 21 only. A comparison of the replication pattern and of the activity of superoxide dismutase (gene located on chromosome 21) shows a clear correlation between late replication, gene inactivation and phenotype expression of chromsome 21.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

1981
1981
2005
2005

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(22 citation statements)
references
References 13 publications
1
21
0
Order By: Relevance
“…In human constitutional pathology, various conditions were described: loss of the alternate inactiva tion of X chromosomes of paternal and maternal origin ; spreading of the late replication inactivation from the late replicating X to autosomal translocated segments (Couturier et al" 1979;Mohandas et al, 1981a, b); and change of the replication pattern of the late replicating X (Dutrillaux et al" 1976;Biémont et al, 1978). To our knowledge, a possible reactivation of the late replicating X has never been described, probably because a functional disomy of the X chromosome is very deleterious (Couturier and Dutrillaux.…”
Section: Discussionmentioning
confidence: 99%
“…In human constitutional pathology, various conditions were described: loss of the alternate inactiva tion of X chromosomes of paternal and maternal origin ; spreading of the late replication inactivation from the late replicating X to autosomal translocated segments (Couturier et al" 1979;Mohandas et al, 1981a, b); and change of the replication pattern of the late replicating X (Dutrillaux et al" 1976;Biémont et al, 1978). To our knowledge, a possible reactivation of the late replicating X has never been described, probably because a functional disomy of the X chromosome is very deleterious (Couturier and Dutrillaux.…”
Section: Discussionmentioning
confidence: 99%
“…Band-sized regions of chromosomes replicate at different times in the cell cycle. Regions of chromosomes which replicate late in the cell cycle are be lieved to contain genes which are inactivated during differentiation [Couturier et al, 1979;Shafer and Priest, 1984], The X chromo somes in mammalian females provide the clearest example of this phenomenon, since one X chromosome in each somatic cell is inactivated and this is the chromosome which is known to replicate late in the cell cycle. Other studies have shown tissue spe cific differences in replication patterns that are associated with developmental differ ences in gene expression [Willard, 1977;Latt et al, 1981;Shafer and Priest, 1984], Differ ences in replication patterns between species would suggest that some regulatory genes were being activated differently across spe cies, while shared patterns would suggest common ancestry.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that each X-linked gene has associated with it specific sequences that are able to bind both activator and repressor proteins and that the combination of these sites for any single gene determines whether it will be subject to inactivation (5). However, analysis of human X;autosome translocations indicates that such putative gene-specific elements must not be restricted to X-linked genes, because autosomal genes that are translocated to the X chromosome can either remain active (6)(7)(8) or be inactivated (7,(9)(10)(11)(12). Further, expression analysis of autosomal transgenes inserted into the mouse X chromosome also implies that such gene-specific elements must be reasonably widespread in mammalian genomes (13,14).…”
mentioning
confidence: 99%